More Sensitive Identification for Bradykinesia Compared to Tremors in Parkinson’s Disease Based on Parkinson’s KinetiGraph (PKG) - Chen, Lina; Cai, Guoen; Weng, Huidan; Yu, Jiao; Yang, Yu; Huang, Xuanyu; Chen, Xiaochun; Ye, Qinyong (Frontiers in Aging Neuroscience, 2020)
The effective management and therapies for Parkinson’s disease (PD) require appropriate clinical evaluation. The Parkinson's KinetiGraph (PKG) is a wearable sensor system that can monitor the motion characteristics of PD objectively and continuously .This study was aimed to assess the correlations between PKG data and clinical scores of bradykinesia, rigidity, tremor and fluctuation.It also aims to explore the application value of identifying early motor symptoms.An observational study of 100 PD patients wearing the PKG for ≥ 6 days was performed. It provides a series of data, such as the bradykinesia score (BKS), percent time tremor (PTT), dyskinesia score (DKS), fluctuation and dyskinesia score (FDS). PKG data and UPDRS scores were analyzed, including UPDRS III total scores, UPDRS III-bradykinesia scores (UPDRS III-B: items 23-26, 31), UPDRS III-rigidity scores (UPDRS III-R: item 22) and scores from the Wearing-off Questionnaire (WOQ-9). This study shows that there was significant correlation between BKS and UPDRS III scores, including UPDRS III total scores, UPDRS III-B and UPDRS III-R scores (r: 0.479-0.588, p ≤0.001), especially in the early-stage group(r = 0.682, p < 0.001). Furthermore, we found that BKS in patients with left-sided onset (33.57±5.14, n=37) is more serious than in patients with right-sided onset(29.87±6.86, n=26). Our findings support the feasibility of using the PKG to detect abnormal movements, especially bradykinesia in PD. And it is suitable for the early detection,remote monitoring and timely treatment of PD symptoms.